Recommending the addition of the Little Beaver Creek, Ohio, to the national wild and scenic rivers system : message from the President of the United States . February 10, 1976. - United States. President (1974-1977 : Ford) (Washington : U.S. Govt. Print. Off., 1976)
Mode of access: Internet.